The Enhancement of Senior High School Students’ Analytical Thinking Skills in Learning Excretory System Material with Quantum Learning Model - Mardiansyah, Eka Aprilia; Saptono, Sigit; Setiawati, Ning (FMIPA UNNES, 2019)
High-level thinking skills are incredibly required to face the challenges in the 21st-century era. One of it skill is to think analytically or people commonly call it analytical thinking. Analytical thinking skills can be trained to the students with an effective learning model. This study aims to describe the enhancement of the analytical thinking skills of high school students on the learning of excretory system materials with quantum learning model. The subject in this study students grade XI in SMA Negeri 1 Boja, and MA Al-Asror which each of 2 classes of treatment. This research design is a quasi-experimental, with non-equivalent design pretest-posttest. Documentation, tests, questionnaires, and interviews are used as data collection techniques. The enhancement of students' analytical thinking skills on learning of excretory system materials with quantum learning model as primary data was analyzed with N-gain. The result of data analysis showed an increase of average analytical thinking skills of N-gain in both treatment class of MA Al-Asror of 0,53 with the medium category and in both treatment class of SMA Negeri 1 Boja equal to 0,79 with the high category. The secondary data result the average percentage of student activity in MA Al-Asror 79% and SMA Negeri 1 Boja 81,1%, both percentages are classified into a nice category. The analysis students questionnaire assessment in MA Al-Asror is 81% with effective category and SMA Negeri 1 Boja is 82% with the very effective category. The result of the analysis of teacher questionnaire assessment in MA Al-Asror is 75% with effective category and SMA Negeri 1 Boja is 97,5% with the very effective category. Interviews with students and teachers being presented by descriptive. Analytical thinking skills covering of identifying, distinguishing, and linking cause and effect is increased in learning of excretory system material with quantum learning model.